Penggunaan Edlink untuk Kemudahan Proses Perkuliahan Mahasiswa FEBI IAIN Lhokseumawe di Masa Pandemi Covid-19 - Angga Syahputra; Khalish Khairina; Husna Hayati; Heny Rofizar; Asmah Savitri (Jurnal Abdimas Ekonomi dan Bisnis, 2021)
The Covid-19 pandemic has forced various parties to use technological innovations in the lecture process so that students can continue to receive knowledge safely and vice versa with lecturers. Unfortunately, the use of technology in lectures has various negative impacts for students and other users. For this reason, the service team disseminates the use of learning applications that can minimize the negative impacts that exist through the use of the Edlink application. This activity was carried out using the Edlink usability socialization method, practice of using it, and question-and-answer discussions about this application. This activity was attended by residents of the FEBI IAIN Lhokseumawe campus consisting of students and lecturers who attended in person or virtually, considering the progress that had to be carried out. The results of this activity are felt to be very useful for lecturers and students in particular. With various features and conveniences in the Edlink application, this application is believed to be able to facilitate the lecture process. This application is also integrated with the Siakad application which has been used in the lecture process, so that the lecture process is more effective and efficient. The Edlink application can also be accessed freely via a computer, laptop or mobile phone and is free. Thus eliminating the limitations that exist in other applications and reducing internet costs for students.